An annotated catalogue of Iranian Aulacidae, Evaniidae and Gasteruptiidae (Hymenoptera: Evanioidea) - Ghahari, Hassan; Madl, Michael (Zootaxa, 2017)
Currently 36 species of the superfamily Evanioidea are recorded from Iran. The family Aulacidae is represented by four species belonging to the genus Pristaulacus Kieffer, 1900), Evaniidae by five species belonging to three genera, Brachygaster Leach, 1815 (one species), Evania Fabricius, 1775 (three species), Prosevania Kieffer, 1911 (one species), and Gasteruptiidae by 27 species belonging to the genus Gasteruption Latreille, 1796.